Ice rafting, Ocean circulation and Glacial activity on the western Svalbard margin 0–74 000 years BP - Jessen, Simon Pind (UiT Norges arktiske universitet, 2015)
The papers of this thesis are not available in Munin: I: Jessen, S.P., T. L. Rasmussen, T. Nielsen, and A. Solheim. 2010: 'A new Late Weichselian and Holocene marine chronology for the western Svalbard slope 30,000-0 cal years BP', available in Quaternary Science Reviews 29, 1301-1312 II: Jessen, S. P., and T. L. Rasmussen (submitted). 'Sortable Silt Cycles in Svalbard Slope Sediments 74-0 ka', submitted to Journal of Quaternary Science, submission no. JQS-15-0006 III: Jessen, S. P., and T. L. Rasmussen: 'Ice rafting patterns on the western Svalbard slope 74-0 ka: Interplay between ice sheet activity and ocean circulation', manuscript to be submitted to Paleoceanography IV: Rasmussen, T. L., E. Thomsen, M. A. Ślubowska, S. P. Jessen, A. Solheim, and N. Koç. 2007. 'Paleoceanographic evolution of the SW Svalbard margin (76°N) since 20,000 14C yr BP', available in Quaternary Research 67, 100-114 The thesis builds on 11 sediment cores from c. 600 to 1900 m water depth from the continental slope west of Svalbard and one core from the Barents Sea shelf. Together, the cores cover the last 74,000 years. The primary goal was to gain a better insight in ocean circulation and glacial activity in a climatic context on glacial-interglacial and millennial time scales. The main parameters studied are ice rafted detritus (IRD) - i.e. sand grains transported out to sea by icebergs or sea ice, grain-size of sortable silt (10-63 micron), which measures the strength of bottom currents, and the magnetic susceptibility of sediments, a proxy for sediment provenance and current activity. The main findings are: - The Svalbard-Barents Sea ice sheet reached the shelf break before 24,000 years BP, when it was at its maximum size. The timing of maximum glaciation is monitored by series of mass transport deposits along the entire slope. The timing is at least 3000 years earlier than previously reconstructed. - The ice sheet was at its largest size for a relatively short time. The initial glacial retreat occurred no later than 21,000 years ...